A framework for the taxonomy and assessment of new and emerging transport technologies and trends - Gkoumas, Konstantinos; Tsakalidis, Anastasios (Transport, 2019)
This paper focuses on the development of a taxonomy framework for new and emerging technologies and trends in the transport sector. This framework is proposed towards the assessment and monitoring of the acceptance, impact and diffusion of technologies and trends, together with a scoring system and a front–end visualisation of the outcomes. In this context, an overview of the transport technology hype over the last years and the establishment of future transport technologies and trends is provided. Issues arising from different constraints, including technological and technical, are taken into account, also considering the transport sector’s interconnection with other sectors and potentially related bottlenecks and drawbacks. The paper outcome is a methodological framework for the creation of different taxonomies for new and emerging transport technologies and trends, achieved through the quantitative assessment of the attractiveness and competitiveness, in terms of diffusion potential, of emerging transport technologies and trends, by associating explicit indices to the various elements of the taxonomies. The proposed taxonomy, assessment and monitoring framework supports innovation management through the identification and evaluation of new and emerging technologies and trends in the field of transport at various levels, thus providing insights to the sector’s stakeholders, while backing the current transport systems’ transformation through technological advances.First published online 10 May 2019